Etika Kepemilikan dan Distribusi Kekayaan Digital: Perspektif Filsafat Ekonomi Islam tentang Falah Sosial - Fathri Varanzhi; Adit Tri Kurniawan; M. Mustofa Tri Buana; Havis Aravik (TOMAN: Jurnal Topik Manajemen, 2026)
The digital economy has generated new forms of wealth, including data, digital assets, and technological platforms, which potentially intensify inequality and wealth concentration. This article examines the ethics of ownership and distribution of digital wealth from the perspective of Islamic economic philosophy with an orientation toward social falah. This study employs a qualitative library research approach by reviewing literature on Islamic economics, economic ethics, maqasid al-shariah, and contemporary digital economy studies. Data are analyzed using a descriptive-analytical method with a philosophical-normative approach to explore ownership as a trust, distributive justice, the role of the state, and transcendent ethics. The findings indicate that digital wealth is not an absolute individual right but a trust requiring social responsibility. The maqasid al-shariah framework positions social falah, encompassing material and spiritual well-being, as the primary orientation of digital wealth management. Therefore, ethical integration and just distribution are essential for a sustainable Islamic digital economy.